Euroscepticism in France: An analysis of actors and causes - Xhulia Likaj; Lena Rieble; Laura Theuer (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2020)
This paper discusses the development of Euroscepticism in France and the underlying actors and causes. First, the literature review presents a selection of distinct classifications, actors and sources for the analysis. Thus, the distinction between hard and soft Euroscepticism as well as diffuse and specific support for European integration guides the interpretation of Eurobarometer data, which show that there has been an actual increase of French discontent towards the European project since the early 1990s. The Front National represents the main actor within the Eurosceptic landscape. A socio-demographic analysis of the electorate describes the average frontiste likely to be a male, belonging to a household with lower levels of income and education, and besides immigration and security, ranking identity and national sovereignty very highly on their list of concerns. Eventually, the sources for rising Euroscepticism in France are examined in light of socio-economic, cultural and institutional factors. Once more, Eurobarometer data reveal that while economic concerns tend to fuel EU-critical positions rather than fundamental opposition, cultural aspects like national identity, immigration and national security should also be deemed as a crucial source of Euroscepticism. Institutional dissatisfaction at the national and European level -particularly related to the mismanagement of the financial and sovereign debt crisis as well as the migration crisis - has also contributed to the amplification of EU-critical attitudes.
Keywords: 330; Euroscepticism; France; Front National; Rassemblement National; Euro Crisis; Migration Crisis